2016
DOI: 10.1002/hbm.23126
|View full text |Cite
|
Sign up to set email alerts
|

Brain network dysregulation, emotion, and complaints after mild traumatic brain injury

Abstract: Functional interactions of the executive and salience networks were related to emotion regulation and complaints after mTBI, with a key role for the bilateral frontal network. These findings may have implications for future studies on the effect of psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 63 publications
2
45
0
1
Order By: Relevance
“…The dFC was found to be significantly correlated with the frequency of headache for the PPTH group and the intensity of pain for the migraine group. sFC and dFC may therefore be useful for exploring the pathophysiological mechanisms in PPTH and migraine [16]. Although it is hard to connect preclinical works and patients' experience, visual stimuli could accentuate the migraine pain following the physiological connection existing between the sensory pain processing region and the visual processing region.…”
Section: Sensory Differences Between Migraine and Ppthmentioning
confidence: 99%
“…The dFC was found to be significantly correlated with the frequency of headache for the PPTH group and the intensity of pain for the migraine group. sFC and dFC may therefore be useful for exploring the pathophysiological mechanisms in PPTH and migraine [16]. Although it is hard to connect preclinical works and patients' experience, visual stimuli could accentuate the migraine pain following the physiological connection existing between the sensory pain processing region and the visual processing region.…”
Section: Sensory Differences Between Migraine and Ppthmentioning
confidence: 99%
“…Mindfulness is a form of meditation, which is derived from Buddhism and involves focusing one's attention to the present moment, maintaining awareness and control of present thoughts, feelings and sensations, and observing them without judgment [70]. Interestingly, fMRI studies have shown that mindfulness increases activity of areas within the salience network [71], reduces default mode network activity [72], and alters the functional collaboration between the salience, executive, and default mode networks [65].…”
Section: Neural Network and Emotion Regulationmentioning
confidence: 99%
“…Typically, these deficits are assessed individually per task (e.g., identified cognitive deficits); however, the influence of psychological response on physical or cognitive outcomes has received limited consideration. Neurobiological supporting evidence potentially linking psychological outcomes with chronic post-concussion alterations include both altered frontal-alpha symmetry on EEG assessment and dorsolateral prefrontal cortex connectivity, which have been associated with the neural substrates underlying psycho-affective health (Chen et al, 2008; Moore, Sauve, & Ellemberg, 2016; van der Horn et al, 2016). Interestingly, postural control testing of gait termination, a functional task with dorsolateral prefrontal cortex supraspinal control, has identified deficits post-concussion which provides further potential evidence linking the systems (Buckley, Munkasy, Tapia-Lovler, & Wikstrom, 2013; Oldham, Munkasy, Evans, Wikstrom, & Buckley, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the hippocampus, amygdala, and prefrontal cortex brain regions are associated with depression and anxiety and neuroimaging investigations have identified physiological alterations in these regions following a concussion (Chen, Johnston, Petrides, & Ptito, 2008; McAllister et al, 2014; Reger et al, 2012; Sheline, Wang, Gado, Csernansky, & Vannier, 1996; van der Horn, Liemburg, Aleman, Spikman, & van der Naalt, 2016). There is also an association between lower functional connectivity in the bilateral frontal and salience network with elevated depression scores following concussion (van der Horn et al, 2016). Similarly, post-concussion metabolic alterations in the kynurenine pathway correlates with elevated anxiety levels (Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%